Animal welfare concepts and strategy for poultry production: a review - Moura, DJ; Nääs, IA; Pereira, DF [UNESP]; Silva, RBTR; Camargo, GA (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
Well being of animals had been historically a public concern, since the beginning of human kind history. As world's population grows there is a need for food including meat. In the last decades there has been a great improvement in poultry production based on the careful control of several aspects, among which nutrition and management (environment, health and rearing systems). Nowadays, the search for good welfare conditions is a global tendency in animal production; however issues surrounding farm animal welfare or well-being, such as definitions, measurements, interpretation, and perception, continue to be controversial. It is known that the result of a broiler not adequately housed is a direct loss in production which leads towards a thought that health, welfare and productivity are intimately connected. In the other hand hints are found in the observation of behavioral responses as well as vocalization, which may provide more precise assessment to welfare. This has been possible due to the use of information technology applied to the field of ethology as well as the multidisciplinary view of the problem. This text provides a review on broiler's welfare issues since its definition to several way of trying to assess it adequately.
Keywords: Bird welfare; housing; behavioral pattern; welfare assessment